The effect of an 8-week low carbohydrate high fat (LCHF) diet in sub-elite Olympic weightlifters and powerlifters on strength, body composition, mental state and adherence: A pilot case-study - Chatterton, S.; Zinn, C.; Helms, E.; Storey, A. (Journal of Australian Strength and Conditioning, 2017)
The effect of low carbohydrate, high fat (LCHF) diets on performance in weight-class restricted strength athletes is inconclusive. However, an LCHF diet could be an effective weight-loss strategy for competition preparation, provided strength is maintained. This study examined the LCHF utility, quantitatively and qualitatively, in five sub-elite level Olympic weightlifters and powerlifters during an 8-week intervention. Two sub-elite Olympic weightlifters and three sub-elite power lifters completed an 8-week LCHF intervention. Carbohydrate was reduced to 1g/kg/day, protein maintained at baseline levels and fat eaten ad libitum. Pre-and post-quantitative measures included strength performance, skinfold measurements, muscle ultrasound imaging and a psychometric questionnaire (recorded daily). Qualitative measures included a written questionnaire and post intervention in-person interviews. Four out of five participants reduced body weight (2.1-3.6 kg). Three participants` skinfolds decreased (11.0-27.3 mm). Two participants` strength increased after the intervention similarly to retrospective performances; two participants` strength remained unchanged; one participant`s absolute and relative strength decreased. DALDA analysis showed statistically significant trends (p<0.05) in multiple participants for "tiredness" and "need for rest" with a greater prevalence of `worse than normal` scores during the intervention. Low energy and fatigue were identified as common themes during the initial weeks of the LCHF intervention. Overall, the participants found the diet acceptable for their training and lifestyle. An 8-week LCHF diet had no detrimental effect on performance in four of five athletes, yet allowed for a reduction in body weight and skinfolds. An LCHF diet could be appropriate for strength athletes when timing, training phase, lifestyle and individual food preferences are considered. Future research should target a larger cohort to investigate possible LCHF benefits for strength athletes.